2014
DOI: 10.1038/srep05280
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion on a superhydrophobic ratchet

Abstract: Liquids in the Leidenfrost state were shown by Linke to self-propel if placed on ratchets. The vapour flow below the liquid rectified by the asymmetric teeth entrains levitating drops by viscosity. This effect is observed above the Leidenfrost temperature of the substrate, typically 200°C for water. Here we show that coating ratchets with super-hydrophobic microtextures extends quick self-propulsion down to a substrate temperature of 100°C, which exploits the persistence of Leidenfrost state with such coatings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 14 publications
(27 reference statements)
3
41
0
1
Order By: Relevance
“…Distilled water meets these substrates with an advancing angle of θ A ≈ 171 ± 2 • and a receding angle of θ R ≈ 165 ± 2 • . These high values and the corresponding low hysteresis θ = θ A − θ R ≈ 6 • characterize a superhydrophobic Cassie state: liquid only contacts the tops of the hydrophobic colloids, which minimizes the pinning of contact lines and viscous dissipation (Gogte et al 2005;Olin et al 2013;Dupeux et al 2014). In such a state, the height H of a puddle becomes nearly independent of the contact angle and it tends towards twice the capillary length 2a = 2(γ /ρg) 1/2 (i.e.…”
Section: Observationsmentioning
confidence: 97%
“…Distilled water meets these substrates with an advancing angle of θ A ≈ 171 ± 2 • and a receding angle of θ R ≈ 165 ± 2 • . These high values and the corresponding low hysteresis θ = θ A − θ R ≈ 6 • characterize a superhydrophobic Cassie state: liquid only contacts the tops of the hydrophobic colloids, which minimizes the pinning of contact lines and viscous dissipation (Gogte et al 2005;Olin et al 2013;Dupeux et al 2014). In such a state, the height H of a puddle becomes nearly independent of the contact angle and it tends towards twice the capillary length 2a = 2(γ /ρg) 1/2 (i.e.…”
Section: Observationsmentioning
confidence: 97%
“…[ 44 ] Note that the formation of an integral fi lm during the Leidenfrost regime is not benefi cial for evaporation-based thermal management applications such as in the spray cooling of electronic devices. On surfaces with larger ratchet structures, [162][163][164] the vapor fl ow is dominant and the Leidenfrost drop shifts against the tilted direction, whereas the drop moves along the tilted direction for surfaces with tiny features (Figure 6 e). [ 165,166 ] Li et al reported that a directional rebounding towards the higher heat transfer region can be achieved through breaking the wetting symmetry at high temperature.…”
Section: The Effect Of Air Lubrication For Fast Drop Bouncingmentioning
confidence: 99%
“…Moreover, Grounds et al [19] have experimentally studied the processes that Leidenfrost droplets climb uphill on tilted ratchet surfaces with different sub-structures. Recently, Dupeux et al [20] reported that the water droplets can be propelled far below the usual Leidenfrost temperature when using textured superhydrophobic ratchets, which extends the parameter range where self-propulsion can be obtained. Using a low pressure environment, Celestini et al [21] found that the Leidenfrost droplets of water can be generated at room temperature.…”
Section: Introductionmentioning
confidence: 96%